Gender Stereotype towards SDGs in Indonesia - Noviyanti Soleman; Rifki Elindawati (IAIN TERNATE, 2019)
Sustainable development goals (SDGs) is blueprint for peace and prosperity for people and the planet, now and into the future. SDGs is an agenda to be reach at 2030 with 17 goals. Sustainable Development Goals is officially adopted by 193 members state of United Nation since September 2015. Indonesia is involved in those 193 members state. Since 1950, Indonesia was admitted as 60th member state of United Nations. As the United Nation member state, Indonesia actively adopted the Sustainable Development Goals. How ever Indonesia still have to face gender stereotype in all aspects with the indicators of religion, ethnic, sex, culture and others. It has strong relationship with patriarchy culture. This research is aims to know how the gender stereotype affected the sustainable development goals in Indonesia. The author use qualitative research method by compile the secondary data and analyzing through thematic analysis approach. The result shows that five from 17 goals has stereotype from society in every single goal. The background reason of stereotype is come from culture, behavior, religion, ethnic and other social reason.